Online Da’wah on Social Media: Personal Branding of a Female Celebrity Preacher on Instagram - Siti Mutmainah; Sayidah Afyatul Masruroh; Agoes Moh Moefad; Izzatul Muwahhidah (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2022)
Branding a public persona for a religious preacher in today's digital era is more accessible thanks to social media platforms such as Instagram. Personal branding is essential for boosting a preacher's credibility, which increases public trust. Therefore, this paper aims to reveal the implementation of personal branding for da'wa by a famous female celebrity preacher, Oki Setiana Dewi, who has been active in online da'wa for over a decade. Data for this paper were mainly obtained by documenting Oki Setiana Dewi's Instagram account (@okisetianadewi). The content analysis technique was applied to qualitatively and descriptively analyze the collected data. The findings of this research show that eight principles are actively used in da'wa personal branding: specialization, leadership, personality, difference, visibility, unity, firmness, and good name. Oki Setiana Dewi consistently displays various da'wa content in photos, videos, and written captions to build her image as a female preacher.